Kekuatan Jempol Gen-Z: Peran Media Sosial dalam Mendorong Proses Digital terhadap Kebijakan DPR - Ramadhani, Annisa; Aisyah, Sabrina Nur; Auliya, Shuhufa Nur Indah (Maliki Interdisciplinary Journal, 2026)
Gen Z is an essential generation in achieving the “Indonesia Emas” 2045 vision. Although often perceived as politically indifferent, they are actually active in driving changes in political culture through social media. As digital natives, Gen Z uses platforms such as TikTok, Instagram, and X to share information, voice opinions, and advocate for social and political issues, including human rights and social justice.The main problem addressed in this qualitative descriptive research is how the role of social media, driven by Gen Z, effectively encourages digital protests and influences the policymaking process of the House of Representatives (DPR), as well as the challenges it faces. The study concludes that social media has transformed into a powerful mechanism for public oversight and accountability, positioning Gen Z as a key driver of political digitalization. Their participation has been shown to influence the DPR, such as during the #TolakRUUOmnibusLaw campaign in 2020, which pushed the DPR to revise controversial articles, as well as in their close monitoring of the Asset Confiscation Bill and the Criminal Procedure Code Bill, which even compelled DPR leaders to respond directly during a Plenary Session.The uniqueness of this study lies in its content analysis, which shows the shift of social media from a communication tool to a strong system of public oversight, led by Gen Z. However, challenges such as the spread of hoaxes and disinformation, as well as excessive dependence on technology, remain. This situation calls for improved digital literacy and moral education.